Artykuł oryginalnyNT-proBNP in patients after acute coronary syndrome with ST segment elevation subjected to early posthospitalization cardiologic rehabilitation - Irzmański, Robert; Piechota, Mariusz; Barylski, Marcin; Banach, Maciej; Kowalski, Jan; Serwa-Stępień, Ewa; Drożdż, Jarosław; Pawlicki, Lucjan (Archives of Medical Science, 2006)
Introduction: In the group of patients with acute coronary syndromes, both BNP (brain natriuretic peptide) and NT-proBNP provide independent and additional diagnostic information and have high predictive value. The aim of the study was to estimate NT-proBNP concentrations under the effect of exercise training in patients following myocardial infarction with ST segment elevation, treated with primary PTCA and intracoronary stent placement. Material and methods: The examinations were performed in two groups matched as regards age, gender, infarction location, risk factors and troponin level. Group I included 17 men, who within the last 2-3 weeks had acute coronary syndrome with ST segment elevation and were treated with primary angioplasty and intracoronary stent placement. These patients were qualified for 12-day exercise training. Group II comprised 14 men, who for the same reasons were treated with primary angioplasty but according to the risk stratification criteria for patients qualified for rehabilitation were not subjected to rehabilitation exercises on a cycloergometer. Results: In group I, after exercise cycle completion a statistically significant decrease in NT-proBNP concentration was observed. In group II, no statistically significant change in NT-proBNP concentration was noted. In group I, a statistically significant increase in EF was detected and in group II, EF did not improve significantly after the period of observation. Both in group I and II a significant negative correlation was observed between NT-proBNP concentration and EF. Conclusions: Taking into account that NT-proBNP is a sensitive and specific marker of left ventricular function, the results of our studies confirm the value of cardiologic rehabilitation as a useful therapeutic method in patients after myocardial infarction, making easier the restoration of normal left ventricular function.